How do Leading Retail MNCs Leverage CSR Globally? Insights from Brazil - Barin Cruz, Luciano (Journal of business ethics, 2010)
This study examines how multinational corporations (MNCs) from the retail sector deal with four challenges they face when adopting Corporate Social Responsibility (CSR) policies: the challenge of developing well-performing CSR projects and programs, building competitive advantages based on CSR, responding to local stakeholder issues in the host countries and learning from different CSR experiences on a worldwide basis. Based on in-depth case studies of two globally leading retail MNCs (with strong operations in Latin America), the concept of Transverse CSR Management emerged. Transverse CSR Management is defined as a distinctive form of organizational configuration that crosses different functional areas, country operations, and the boundaries of the firm. In particular, this article makes three main contributions: (1) we identify four central challenges faced by MNC managers when developing their CSR strategies; (2) we propose the concept of Transverse CSR Management to face these central challenges (together, at the same time) and identify its key elements (top management, external stakeholders, functional areas, and country subsidiaries); and (3) we propose four mechanisms (hierarchical, relational, cultural, and collaborative) through which the concept of Transverse CSR Management can be implemented by practicing managers. This study provides valuable insights for MNC managers in headquarters and subsidiaries on the issues they need to address in order to successfully deal with the four CSR-related challenges.